(untitled) (Editora Impacto Científico, 2025)
Contemporary higher education involves an academic formation process that combines integrative activities between theory and practice to strengthen critical thinking, community engagement, and the practical application of knowledge. This article aims to evaluate the contribution of Scientific Initiation (SI) to academic training, the development of students’ skills, and the advancement of scientific research in Brazil during undergraduate studies. Additionally, it seeks to identify the limitations and barriers faced by SI within the national context. To achieve this, a documentary research was conducted, based on articles exploring the concept, objectives, and impacts of this practice on qualification in specific areas of knowledge. The results demonstrated that SI plays a fundamental role in academic development by encouraging scientific, technical, and social skills essential for students’ education. The research also highlights how scientific practice contributes to building a solid critical foundation, fostering undergraduate students’ engagement in research activities, and preparing them for successful academic and professional careers. It is concluded that this study is relevant in evidencing the positive impact of SI on academic and scientific formation, reinforcing its importance as an essential pillar for developing competencies that transcend classroom boundaries.